I want to quit education: A longitudinal study of stress and optimism as predictors of school dropout intention. Issue 7 (15th August 2014) - Eicher, Véronique; Staerklé, Christian; Clémence, Alain
ABSTRACT: Prior research on school dropout has often focused on stable person‐ and institution‐level variables. In this research, we investigate longitudinally perceived stress and optimism as predictors of dropout intentions over a period of four years, and distinguish between stable and temporary predictors of dropout intentions. Findings based on a nationally representative sample of 16–20 year‐olds in Switzerland ( N  = 4312) show that both average levels of stress and optimism as well as annually varying levels of stress and optimism affect dropout intentions. Additionally, results show that optimism buffers the negative impact of annually varying stress (i.e., years with more stress than usual), but not of stable levels of stress (i.e., stress over four years). The implications of the results are discussed according to a dynamic and preventive approach of school dropout.